Stochastic processes and models - Stirzaker, David (Oxford ; New York : Oxford University Press, 2005)
The book provides a concise and lucid introduction to simple stochastic processes and models. Including numerous exercises, problems and solutions, it covers the key concepts and tools, in particular: random walks, renewals, Markov chains, martingales, the Wiener process model for Brownian motion, and diffusion processes, concluding with a brief account of the stochastic integral and stochastic differential equations as they arise in option-pricing.
Includes index.
Includes bibliographical references: p. 323.
rpm 24/05/2013
Loans
Keywords: Stochastic processes; Stochastic models